HUBUNGAN ANTARA KECEMASAN DENGAN TEKANAN DARAH PADA PASIEN PREOPERASI DI RUMAH SAKIT GRAHA HUSADA BANDAR LAMPUNG - Nabilla Syafira; Roro Lintang Suryani; Tin Utami (Jurnal Inovasi Penelitian, 2023)
The negative impact of anxiety in the preoperative phase is very large in the occurrence of complications in patients in the form of bleeding if there is a significant increase in blood pressure so that prevention efforts are needed so that it does not occur. The purpose of this study was to determine the relationship between anxiety and blood pressure in pre-operative patients at Graha Husada Hospital Bandar Lampung in 2022. The type used in this study was quantitative. The research design used in this study was correlation analytic with a cross sectional approach to research implementation. This study was conducted from January to August and data collection will be planned on August 1 – August 25, 2022. The number of samples in this study were 70 respondents and the statistical test used was the Chi-square test. The results of the study were more respondents who experienced mild anxiety, namely 34 (48.6%). And more respondents who experienced early stage 1, namely 34 (48.6%), and there was a relationship between blood pressure anxiety in patients before surgery at home. Graha Husada Hospital Bandar Lampung in 2022 with a p value of 0.001